Influence of Sense of Competence, Empathy and Relationship Quality on Burden in Dementia Caregivers: A 15 Months Longitudinal Study. (March 2023) - Kieboom, Robin van den; Mark, Ruth; Snaphaan, Liselore; Assen, Marcel van; Bongers, Inge
Objectives: The aim is to explore the trajectory of caregiver burden and how this relates to caregiver and contextual factors in community-dwelling dyads.Methods: At baseline, 201 family caregivers were included. The multidimensional construct of family caregiver burden and the effects of sense of competence, empathy, and quality of the relationship on this burden were assessed over 15 months using semi-structured interviews and questionnaires.Results: We found an increase of burden linked to disruptions in the caregiver's own usual activities ( p = 0.002) and physical health complaints ( p = 0.001). Caregivers with a high sense of competence experienced lower caregiver burden during the entire caregiving process ( p < 0.001).Discussion: Healthcare professionals should alert family caregivers to the importance of taking care of themselves as early as possible in their new caregiver role. Caregiving is demanding and could negatively influence their own activities and physical health.